Tilted fiber bragg grating vibration sensor intended for use in deep-sleep diagnosis - Quek, Andrew Zhi Wei. (2010)
This final year report seeks to document that a TFBG inscribed in a SMF and a spliced MMF section is able to detect mechanical vibrations with the exhibition of strong correlation to the frequency of the vibrations. The mechanical vibration or dynamic bending action on the fiber optical sensor (FOS) region will lead to vibration dynamics being embedded in the enhanced optical cladding modes that back propagate after reflectance in the FOS region. The optical manifestations that result from the vibrations appear as fluctuations in the cladding mode optical power. The relationship between the time-domain power wave forms (traced by the optical power fluctuations during vibration sensing) is a full reflection of the actual vibration frequencies that is enacted on the FOS. The traits inferred during the characterization experiments showed that the fabricated FOS is able to effectively sense vibrations from 0Hz till 30Hz, presented good SNRs at frequencies which generate optical power maximums and has a sensitivity of 33.638 nW per millimeter of vibration deviation effectuated on the vibration sensor. In terms of a potential biomedical application for the fabricated vibration FOS, the sensor could be use in sleep pattern diagnostics. Its implementation can allow realtime recordings of Rapid Eye Movement (REM) spans in a human sleep cycle and aid sleep-disorder clinicians.